2020
DOI: 10.1038/s41598-020-59517-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cyclooxygenase-1 by nonsteroidal anti-inflammatory drugs demethylates MeR2 enhancer and promotes Mbnl1 transcription in myogenic cells

Abstract: Muscleblind-like 1 (MBNL1) is a ubiquitously expressed RNA-binding protein, which is highly expressed in skeletal muscle. Abnormally expanded CUG-repeats in the DMPK gene cause myotonic dystrophy type 1 (DM1) by sequestration of MBNL1 to nuclear RNA foci and by upregulation of another RNAbinding protein, CUG-binding protein 1 (CUGBP1). We previously reported that a nonsteroidal antiinflammatory drug (NSAID), phenylbutazone, upregulates MBNL1 expression in DM1 mouse model by demethylation of MeR2, an enhancer e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Genomic DNA (gDNA) was extracted from peripheral blood (MyGenostics) using a DNeasy Blood and Tissue Kit (Qiagen, Venlo) as previously mentioned 13 , 14 according to the manufacturer's instructions. Next‐generation sequencing (NGS) analysis covering 2082 genes known to be associated with neuromuscular disorders was performed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA (gDNA) was extracted from peripheral blood (MyGenostics) using a DNeasy Blood and Tissue Kit (Qiagen, Venlo) as previously mentioned 13 , 14 according to the manufacturer's instructions. Next‐generation sequencing (NGS) analysis covering 2082 genes known to be associated with neuromuscular disorders was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA (gDNA) was extracted from peripheral blood (MyGenostics) using a DNeasy Blood and Tissue Kit (Qiagen, Venlo) as previously mentioned 13,14 according to the manufacturer's instructions.…”
Section: Genetic Analysismentioning
confidence: 99%
“…The results of this study were analysed and reported in accordance with the STROBE guidelines 8 . The real-time PCR test was performed as previously described with modification 9 , 10 , and was based on the criteria provided by the World Health Organization (WHO) 11 . Nasopharyngeal swabs were taken on the 1st, 7th and 14th days of medical isolation observation.…”
Section: Methodsmentioning
confidence: 99%
“…Two important approaches for the design and synthesis of anti-inflammatory agents are based on the inhibition of two enzymes, cyclooxygenase (COX) and lipoxygenase, both of which are involved in the metabolism of arachidonic acid. Cyclooxygenase (COX) catalyzes the conversion of arachidonic acid to prostaglandins, with COX-1 being the constitutive isoform that is expressed in most tissues, while COX-2 is only expressed when induced by the response to inflammation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%